Peran Dinas Lingkungan Hidup Terhadap PT. Multi Strada Arah Sarana.Tbk Dalam Potensi Pelanggaran Perizinan Lingkungan - Kusuma, Nofan Chandra; Pratama, Dias Ramdani Zulfa; Supriadi, Riziq; Herlian, Sherli; Dina, Asri Ning (Journal of Industrial Relations Studies, 2025)
This study aims to determine the form of licensing violations committed by PT. Multistrada Arah Sarana.Tbk and to analyze the role of the Environmental Service in handling licensing violations of PT. Multistrada Arah Sarana.Tbk. This study uses an Empirical method, namely library materials, observations and interviews with related parties. The results found that environmental licensing violations committed by PT. Multistrada Arah Sarana.Tbk, there were several violations such as changes in production facilities that made the transformation of new environmental approvals and did not have a technical detail permit for storing B3 waste, did not carry out cooperation in managing non-B3 waste whose economic value was based on the agreed agreement letter, and did not have practices to fulfill air emission quality standards. The suggestion from this study is that the Environmental Service after this violation must increase supervision of companies that have the potential or have not met environmental licensing requirements, the novelty of this study emphasizes more on interviews with related parties.